In Vitro Antitumor Activity of a Keggin Vanadium-Substituted Polyoxomolybdate and Its ctDNA Binding Properties - Wen Qi; Ying Qin; Yanfei Qi; Li Guo; Juan Li (Journal of Chemistry)
A Keggin vanadium-substituted polyoxomolybdate, K5PMo10V2O40 (PMo10V2), has been synthesized and it’s antitumor effect against Hela cells was investigated. The calf thymus DNA (ctDNA) binding ability of PMo10V2 was also evaluated by UV-Vis absorption spectra and fluorescence spectra. The identity and high purity of PMo10V2 was confirmed by elemental analysis and IR analysis. And the antitumor activity test of PMo10V2 was carried out on Hela cancer cells line by MTT assay. The results of MTT assay show that PMo10V2 significantly reduced the viability of Hela cells in a dose-dependent manner and exhibited stronger inhibitory activity against Hela cells at an IC50 of 800 μg/mL, which is more effective than the positive control, 5-Fu (P<0.05). The results of the UV-Vis absorption spectra and fluorescence spectra indicated the groove or outside stacking binding between PMo10V2 and ctDNA. These results show that the antitumor activity of PMo10V2 may be caused by the interactions between DNA and PMo10V2.